Clinical, genetic and cytokine markers of retinopathy of prematurity in a cohort of Malaysian infants / Syatirah Abu Yazib - Syatirah, Abu Yazib (2019)
Retinopathy of prematurity (ROP) is preventable childhood blindness happen to premature infants. Young gestational age, low birth weight, and high supplemental oxygen are known to be important clinical risk factors in ROP. Recent evidences suggested there are other factors either in the form of proteins or genetic alteration may play a role in ROP pathogenesis. A total of 221 premature infants were included in the study consisting 80 infants diagnosed with ROP and 141 infants without ROP (Control). Study was investigated in three approaches; clinical risk factors, genetics and cytokine. Statistical analysis were assessed according to three group; Control, ROP and Visuallythreatening ROP (VTROP), which is defined as eyes requiring laser treatment (laser or anti VEGF injections). Clinical data for each patient were collected using a standard pro forma during ROP examinations in routine pediatric screening or retrieved from medical record unit, UMMC and comprehensively reviewed by medical officer. Non-biased whole exome sequencing was done to first 20 consecutive DNA samples of patients diagnosed with 10 of ROP patients and 10 control patients. Single variant was choose, SARDH polymorphism (rs582326) was identified in 5 out of 10 ROP samples and validated by Sanger sequencing validation. The remaining samples (n=201) were tested for the polymorphism using Taqman® Genotyping Assay, AssayID: C__2256321_20. Serum levels cytokines VEGF-A, VEGF-C, VEGF-D, IGFBP1,IL-6, IL-8, IL-18, TGFalpha, TNF-alpha, HB-EGF, ANGPT2, EGF, Endoglin, PLGF, sCD40L, sFASL, PAI-1 and uPA were measured by multiplex protein array, BioPlex Pro™ Human Cancer Biomarker on 69 consecutive serum samples from similar cohort at 36-38 weeks of infant’s gestational ages. Data analysis on clinical risk factors showed significance differences in gestational age, (p<0.001), birth weight (p<0.001), duration of NICU stay (p<0.001), bronchopulmonary dysplasia (BPD), respiratory support (p<0.001) and iv invasive ventilation (p<0.001) between control and ROP/VTROP group. In addition, in multipe logistic regression, patients with younger gestational age (<29 weeks) the risk of having ROP is increase by 88% .As for invasive ventilation, it can be hypothesized as the longer duration of invasive ventilation, increase the odds of having ROP by 7 times and 3 times more likely to develop advance ROP which required a treatment (VTROP).In genetic analysis, there was a poor associations between SARDH polymorphism and ROP in any of genetic models (dominant, recessive and additive), after adjusting for age, birth weight and gender. In addition, significance difference of VEGF-D (p=0.024) and IL8 (p=0.046) level was observed in VTROP compare to Non VTROP group. VEGF-D also found significance (p=0.038) in VTROP versus Control group. Level of other cytokines did not reveal any significance difference among other analyzed groups. All in all, clinical data risk factors analysis shown low gestational age was strongly associated in increased risk of ROP. However, genotyping analysis shows poor association of ROP with SARDH gene (rs582326) in Malaysian population. Though, cytokine analysis shown higher VEGF-D level may be further correlated with vision threatening ROP. All in all, these results were important as to determine potential factors that may contribute to the development of therapeutics and treatment for ROP.